Letter from J. S. Lewis to Ah Louis - J. S. Lewis::::::author:::
Note reads: 'Arroyo Grande June 29th: Ah Louis, Please for 15 [?] Mr. Fowler ($12) Twelve Dol to charge 15 [?] of [?] comply. J. S. Lewis' Reverse side of note reads: 'Received payment, A. Fowler.'